Islam and the West: Coexistence or Clash? - Osmani, Noor Mohammad; Al-Mubarak, Tawfique (Journal of Islam in Asia (E-ISSN 2289-8077), 2012)
Samuel Huntington (1927-2008) claimed that there would be seven eight civilizations ruling over the world in the coming centuries, thus resulting a possible clash among them. The West faces the greatest challenge from the Islamic civilization, as he claimed. Beginning from the Cold-War, the Western civilization became dominant in reality over other cultures creating an invisible division between the West and the rest. The main purpose of this research is to examine the perceived clash between the Western and Islamic Civilization and the criteria that lead a civilization to precede others. The research would conduct a comprehensive review of available literatures from both Islamic and Western perspectives, analyze historical facts and data and provide a critical evaluation. This paper argues that there is no such a strong reason that should lead to any clash between the West and Islam; rather, there are many good reasons that may lead to a peaceful coexistence and cultural tolerance among civilizations